Hysteresis models and fragility assessments of reinforced concrete structural components - Piyali Sengupta (2014)
Earthquakes represent one of the most destructive natural disasters and the extent of casualties and damage in numerous incidences is well documented over the past decades. The devastating consequences of seismic events have emphasized the significance of the structural performance assessment. Fragility function, an essential component in seismic vulnerability estimation, is defined by the conditional probability of a particular structure exceeding a certain damage state when subjected to seismic excitations. Eventually, for development of fragility functions, characterization of the structural behavior and quantification of the structural damage states during seismic events are pertinent. Hence, the present research delineates the structural hysteretic behavior and different stages of damage experienced by reinforced concrete (RC) structural components for derivation of seismic fragility functions. The basic requirement in modeling RC structural components under seismic loading is to define a constitutive load-deformation relationship capable of producing strength and stiffness degradation along with pinching at all displacement levels. This is a demanding task considering the numerous parameters contributing to the structural hysteretic behavior. The Bouc-Wen-Baber-Noori (BWBN) model, owing to its computational efficiency and mathematical tractability, is adopted as the basis of the current research and amended accordingly to simulate the hysteretic behavior of RC structural components. The Livermore Solver for ordinary Differential Equations (LSODE) is employed to solve the differential equations of the model. A database of RC beam-column joints and walls tested under quasi-static loading is compiled from the literature to determine the model parameters by a Genetic Algorithm (GA), a system identification technique and to successfully calibrate the analytical response with the experimental results. Subsequently, the sensitivity ranking of the model parameters is determined and the relationship between the model parameters and the structural features is derived by regression analysis using the existing database of the structural components. To facilitate structural analysis of RC buildings with beam-column joints and walls using the proposed analytical approach, the hysteresis model is effectively implemented as a user element in ABAQUS.